Assessing teamwork : a comparative study of group home teams in Newfoundland and Labrador - Burford, Gale E. (1990)
A combined, multiple-methods action research strategy is constructed and used to assess teams of personnel working in and around group homes for mentally retarded adults and young offenders in the Canadian Province of Newfoundland and Labrador between August, 1983 and January, 1987. Grounded in the practise experiences and previous research of the author, the question "what works?" is developed both as a contextual framework for the examination of teamwork as a component of professional practise and as a contextual feature of group care. The question is used to guide categorization and organization of differences amongst 51 sample teams in order to isolate valid and reliable measures of team work functioning. Drawing from four distinct theoretical traditions comprising core knowledge of human behaviour in the social environment, multiple methodologies for differentiating within and amongst teams are combined to triangulate data around the central research question. A methodology for the collection and analysis of data which are thought to represent the "lived experiences" of sample subjects is developed and used to illuminate the phenomenological alignments of team members. Qualitative themes in the reports of on- and off-the-job satisfactions and frustrations for sample subjects are examined for teams and for occupational groupings. Separate measures of Level of Organizational Change and Prevalence of Stressful working Conditions are developed and used to examine the interplay between these variables and other preselected variables. The assessment procedures and the typology of team functioning developed by Fulcher (1983) are replicated. Specific flaws and limitations in Fulcher's methodology and design are overcome through the use of a different theoretical orientation, extensions and refinements of the methodology, changes in instrumentation and by replicating his findings with a more homogeneous sample. Four of the team styles of adaptation are empirically validated and their descriptions refined. Both ...